Proceedings of the International Conference on Geoinformatics and Data Analysis 2018
DOI: 10.1145/3220228.3220229
|View full text |Cite
|
Sign up to set email alerts
|

A deep learning architecture for sentiment analysis

Abstract: The fabulous results of Deep Convolution Neural Networks in computer vision and image analysis have recently attracted considerable attention from researchers of other application domains as well. In this paper we present NgramCNN, a neural network architecture we designed for sentiment analysis of long text documents. It uses pretrained word embeddings for dense feature representation and a very simple single-layer classifier. The complexity is encapsulated in feature extraction and selection parts that benef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…We involving word embedding, in this case, we applied GloVe [30] and CNN that belonging responsible for generating sentence latent factor vector. As we know that CNN output fit for classification issue [28], [31] and also this approach are not suitable to regression application, So required to incorporating with any method that common use in rating prediction. In our opinion, the matrix factorization method is the right choice to generate rating prediction.…”
Section: Methodsmentioning
confidence: 99%
“…We involving word embedding, in this case, we applied GloVe [30] and CNN that belonging responsible for generating sentence latent factor vector. As we know that CNN output fit for classification issue [28], [31] and also this approach are not suitable to regression application, So required to incorporating with any method that common use in rating prediction. In our opinion, the matrix factorization method is the right choice to generate rating prediction.…”
Section: Methodsmentioning
confidence: 99%
“…In 2018, Cano and Morisio [9] also conducted sentiment analysis using Film Review Data from the IMDB website. The architectural model used is NGramCNN, compared to the SingleCNN and BLSTM-2DCNN models.…”
Section: Related Workmentioning
confidence: 99%
“…It still takes a lot of text data (e.g., many thousands of samples) to generate high-quality embeddings and achieve reasonable classification performance (Ç ano and Morisio, 2017). A neural network architecture for sentiment analysis based on word embeddings is described by (Ç ano and Morisio, 2018). We applied that architecture on the two Czech datasets we are using here and observed that there was severe over-fitting, even with dropout regularization.…”
Section: Preprocessing and Vectorizationmentioning
confidence: 99%